2011
DOI: 10.1371/journal.pone.0017975
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Affects Sperm Viability in a Cricket

Abstract: Recent studies have suggested that males may vary the quality of their ejaculates in response to sperm competition, although the mechanisms by which they do so remain unclear. The viability of sperm is an important aspect of ejaculate quality that determines competitive fertilization success in the field cricket Teleogryllus oceanicus. Using in vitro mixtures of sperm and seminal fluid from pairs of male crickets, we show that seminal fluid can affect the viability of sperm in this species. We found that males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 42 publications
(49 reference statements)
0
50
0
Order By: Relevance
“…Because gene transcription is apparently absent in sperm cells, their functionality is largely dependent on post-translational modifications to their protein compliment that are brought about by sfps. Sfps are known to influence the viability of sperm (den Boer et al 2008, Holman 2009, Simmons & Beveridge 2011 and their motility (Lindholmer 1974, Poiani 2006. In some insect species, Sperm wars seminal fluid has been implicated in the killing of sperm present from rival males (Fry & Wilkinson 2004, den Boer et al 2010, and it has even been suggested that males might exploit the expenditure on sfps made by their rivals, for example, if sfps buffered the female reproductive tract against spermicidal secretions (Hodgson & Hosken 2006).…”
Section: Strategic Adjustments In Seminal Fluid Compositionmentioning
confidence: 99%
“…Because gene transcription is apparently absent in sperm cells, their functionality is largely dependent on post-translational modifications to their protein compliment that are brought about by sfps. Sfps are known to influence the viability of sperm (den Boer et al 2008, Holman 2009, Simmons & Beveridge 2011 and their motility (Lindholmer 1974, Poiani 2006. In some insect species, Sperm wars seminal fluid has been implicated in the killing of sperm present from rival males (Fry & Wilkinson 2004, den Boer et al 2010, and it has even been suggested that males might exploit the expenditure on sfps made by their rivals, for example, if sfps buffered the female reproductive tract against spermicidal secretions (Hodgson & Hosken 2006).…”
Section: Strategic Adjustments In Seminal Fluid Compositionmentioning
confidence: 99%
“…Seminal fluid proteins (SFPs) are being increasingly studied owing to their effects on fertility and female physiology (Poiani, ). SFPs improve male fertility directly, maintaining sperm viability and motility (eg King et al ., ; Simmons & Beveridge, ; Smith & Stanfield, ). Furthermore, many SFPs influence female traits, such as egg production and remating rate (Mane et al ., ; Chapman, ) and are therefore likely targets of selection via sexual conflict (Arnqvist & Rowe, ; Sirot et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recently shown that seminal fluids may play a more direct role in sperm competition by affecting rivals' sperm performance. Indeed, in promiscuous ants and bees seminal fluid incapacitates the sperm of rival males [22], while in other insects it improves equally the survival of own and other sperm [23,24]. This suggests that, unless a self/non-self recognition mechanism evolves [23], the function of seminal fluid to enhance own sperm performance can be exploited by the sperm of rival males [25].…”
Section: Introductionmentioning
confidence: 99%